KNOWLEDGE OF RURAL WOMEN IN NINEVEH TOWARDS CRISIS MANAGEMENT ENVIRONMENTAL AND ITS RELATIONSHIP WITH SOME VARIABLES - Rana Al-Daudee; Wisam Masso (Mesopotamia Journal of Agriculture)
The research aimed to identify the level of knowledge for rural women in reducing environmental crises in Nineveh governorate/ Hamdaniya district, and to determine the correlation between the level of rural women's knowledge in reducing environmental crises with the following independent variables (Age, level of education. Matrimonial Status, Size of Farm Tenure, Participation in Environmental Activities) The comprehensive research was made up of 338 rural women. Data was collected using the questionnaire form for the Hamdaniya district. The Alpha Crow Vegan equation extracted the constant with a survey sample of 30 researchers; the constant was 0.87. After this, data was collected, emptied, and analysed through the Spss programme. The results showed that rural women's knowledge of environmental crisis reduction was moderate and tended to decrease. And also, As to the order of the paragraphs according to their importance, the paragraph (non-dumping of waste in agricultural land) ranked first with an average arithmetic of 0.97 also the results showed the correlation was created Among rural women's knowledge level to reducing environmental crises with a range of independent variables studied, the results shows a correlation between (age, level of education, participation in environmental activities), therefore, the researcher recommends that programmes and efforts aimed at conducting pro-environmental behavioural changes should be intensified and provided with knowledge Encourage them to participate in rural local organizations and contact agricultural extension workers to help them develop their capacities.